Exploiting a robust biopolymer network binder for an ultrahigh-areal-capacity Li–S battery. Issue 3 (21st December 2016) - Liu, Jie; Galpaya, Dilini G. D.; Yan, Lijing; Sun, Minghao; Lin, Zhan; Yan, Cheng; Liang, Chengdu; Zhang, Shanqing
Abstract : High-loading sulfur electrode with ultrahigh areal capacity was easily achieved by exploiting a robust and efficient biopolymer network binder. Abstract : High-loading electrodes play a crucial role in the practical applications of high-energy-density batteries, which are especially challenging for lithium–sulfur (Li–S) batteries. Herein, a mechanically robust network binder was constructed by weaving dual biopolymers ( i.e., guar gum and xanthan gum) via the intermolecular binding effect of extensive functional groups in both polymers. This network binder was capable of effectively preventing polysulfides within the electrode from shuttling and, consequently, improved electrochemical performance. A remarkably high sulfur loading of 19.8 mg cm −2 and an ultrahigh areal capacity of 26.4 mA h cm −2 were achieved as a result of the robust mechanical properties of the network binder. This study paves a new way for obtaining high-energy-density batteries by the simple application of robust network biopolymer binders that are inherently low-cost and environmentally friendly.